2004
DOI: 10.1002/tcr.20006
|View full text |Cite
|
Sign up to set email alerts
|

Femtosecond laser‐induced microstructures in glasses and applications in micro‐optics

Abstract: Femtosecond laser has been widely used in microscopic modifications to materials due to its ultra-short laser pulse and ultrahigh light intensity. When a transparent material e.g. glass is irradiated by a tightly focused femtosecond laser, the photo-induced reaction is expected to occur only near the focused part of the laser beam inside the glass due to the multiphoton processes. We observed various induced structures e.g. color center defects, refractive index change, micro-void and micro-crack, in glasses a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(29 citation statements)
references
References 34 publications
1
26
0
2
Order By: Relevance
“…This study is very close to others [11,24,25] and contributes with a new method for restorative and aesthetic dentistry.…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…This study is very close to others [11,24,25] and contributes with a new method for restorative and aesthetic dentistry.…”
Section: Resultssupporting
confidence: 81%
“…Considering that an all-solid-state tunable Ti:Sapphire continuous wave laser was developed objecting new sources for spectroscopic measurements of various biophotonic information [10] and for micromachining of defects and refractive index change [24]. This study is very close to others [11,24,25] and contributes with a new method for restorative and aesthetic dentistry.…”
Section: Resultsmentioning
confidence: 66%
See 1 more Smart Citation
“…A new approach for the local modification of transparent materials through nonlinear optical processes has been investigated due to extraordinarily high peak intensities of short pulses. A variety of materials including metals, dielectrics, polymers, and semiconductors have been successfully processed by the use of fs pulses [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. Bulk refractive index change in transparent materials is found to be useful in applications of waveguides.…”
Section: Introductionmentioning
confidence: 99%
“…Especially interesting is application of short pulse laser radiation for modification of spherical shape of silver nanoparticles in glass [24-2н]. Optical microscopy studies [24] have shown that irradiation by circularly polarized femtosecond laser radiation can change the spherical shape of silver nanoparticles in glass.…”
Section: F"rmati"n "F Silver Nan"clusters In Ps Glasses By Uv Irradiamentioning
confidence: 99%